Evaluation of Renal Anemia Therapy in Chronic Kidney Disease Patients Undergoing Hemodialysis in Hospital - Joko Arif Kurniawan; Abdul Hakam (Indonesian Journal of Global Health Research, 2026)
End-stage chronic kidney disease (CKD) requiring hemodialysis is often complicated by anemia. Renal anemia in CKD-HD patients can affect quality of life and worsen prognosis. Anemia therapy involves erythropoiesis-stimulating agents (ESAs), iron supplements, and blood transfusions, but evaluation of their effectiveness at Dr. Loekmono Hadi Kudus Regional Hospital is still limited. This study aims to evaluate the anemia profile and the effectiveness of anemia therapy in PGK-HD patients at Dr. Loekmono Hadi Kudus Regional Hospital. This study used a quantitative descriptive method with purposive sampling technique in 93 CKD-HD patients with hemoglobin levels ≤ 10 g/dL. Data were collected through a review of electronic medical records and analyzed using descriptive statistics. Most CKD-HD patients had moderate (48%) and severe (43%) anemia. 90% of patients received ESA therapy, with 62% receiving PRBC transfusions and 47% combination therapy. Iron status analysis showed that many patients required supplemental iron therapy. Anemia in CKD-HD patients at Dr. Loekmono Hadi Kudus Regional Hospital requires more optimal management with routine monitoring of iron status. Further evaluation of ESA and iron therapy is needed to improve patient quality of life and prevent further complications.